CONCEPTUALIZING JUSTICE: POLICE RESPONSES TO SEX CRIMES IN PARTNERSHIP WITH CANADIAN POLICE DEPARTMENTS - Drakes, Keyanna (2017)
Justice exists in and through interpretations of past laws and legal procedures. Justice for sex crimes, however, is particularly complex due to the differences between victim needs and the operations of the criminal justice system. This study, using 70 semi-structured interviews and 2 focus groups from Canadian police departments, shows procedural and distributive justice as the two most prevalent forms of justice police officers use when dealing with sex crimes. The commonalities between the two forms of justice support the notion that police officers have adapted to using multiple methods of justice that are more compassionate to victims of sexual violence. In this paper, I show that Canadian police officers use characteristics from both procedural and distributive justice when responding and dealing with sex victims and their offenders. My analysis shows that police officers are encouraged to use new forms of policing to enhance positive victim relations. Contrary to research that focuses on the adverse treatment of victims, this paper will explore the promising changes in Canadian police officers’ conceptualization of justice for victims and their offender